2013
DOI: 10.1523/jneurosci.5320-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Dependence and Differential Contributions from Somatostatin- and Parvalbumin-Expressing Neurons to Spatial Integration in Mouse V1

Abstract: A characteristic feature in the primary visual cortex is that visual responses are suppressed as a stimulus extends beyond the classical receptive field. Here, we examined the role of inhibitory neurons expressing somatostatin (SOM ϩ ) or parvalbumin (PV ϩ ) on surround suppression and preferred receptive field size. We recorded multichannel extracellular activity in V1 of transgenic mice expressing channelrhodopsin in SOM ϩ neurons or PV ϩ neurons. Preferred size and surround suppression were measured using d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
78
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(91 citation statements)
references
References 58 publications
(12 reference statements)
8
78
1
Order By: Relevance
“…Increasing PVϩ activity likely reduces stimulus drive by controlling the overall responsiveness in the network. Indeed, our observed effects of PVϩ interneuron activation on spatial integration are similar to those obtained when stimulus contrast is lowered (see also Nienborg et al 2013). Consistent with a general modulation of stimulus drive, PVϩ interneurons have recently been implicated in gain control (Atallah et al 2012;Ma et al 2010;Wilson et al 2012).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Increasing PVϩ activity likely reduces stimulus drive by controlling the overall responsiveness in the network. Indeed, our observed effects of PVϩ interneuron activation on spatial integration are similar to those obtained when stimulus contrast is lowered (see also Nienborg et al 2013). Consistent with a general modulation of stimulus drive, PVϩ interneurons have recently been implicated in gain control (Atallah et al 2012;Ma et al 2010;Wilson et al 2012).…”
Section: Discussionsupporting
confidence: 85%
“…To test this hypothesis, we studied surround suppression at different levels of contrast and measured the effects of anesthesia on contrast responses; the results provide support for our hypothesis. First, we confirmed that, just as in cat and monkey, spatial integration in mouse V1 depends on stimulus contrast (see also Ayaz et al 2013;Nienborg et al 2013). At high stimulus contrast (Fig.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…With these results in mind, there is evidence that LGN surround suppression may contribute to the near-surround (Ishikawa et al 2010) and/or the high-contrast summation fields of V1 neurons (Angelucci and Sainsbury 2006; Ozeki et al 2004). The more extensive surrounds of cortical neurons, however, likely rely on 1) feedback from extrastriate areas, which can account for the correct spatial parameters and onset latencies of V1 suppression (Angelucci and Bressloff 2006;Bair et al 2003;Nassi et al 2013), and/or 2) somatostatin-expressing local inhibitory neurons, the optogenetic inactivation of which blocks extraclassical suppression in mouse V1 Nienborg et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the expression of calcium-binding proteins and neuropeptides, interneurons can be classified into distinct groups 14,16,18,19 , among which parvalbumin (PV)-and somatostatin (SOM)-expressing neurons constitute a large fraction 14,19 . Recent studies have used optogenetic techniques to examine how the activities of PV and SOM interneurons influence properties such as cortical response gain, stimulus selectivity and spatial integration [20][21][22][23][24][25] . However, the effect of specific type of inhibitory interneuron on cortical response reliability remains uncharacterized.…”
mentioning
confidence: 99%